The making of Persianate modernity : language and literary history between Iran and India - Jabbari, Alexander (The global Middle East, 2025)
"Tracing the emergence of literary history, Alexander Jabbari shows how Iranians and South Asians drew from their shared literary heritage to produce a 'Persianate modernity' in the nineteenth and twentieth centuries. Using both Urdu and Persian-language sources, Jabbari examines how intellectual exchange across the region made national cultures"--